Silicon valley imperialists create new model villages as smart cities in their own image - Philip Cooke (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
In her study of "Surveillance Capitalism", Shoshana Zuboff cites Google's parent firm Alphabet's legal customer-purchase agreement for the parent firm's Nest thermostats. These impose "oppressive privacy and security consequences" requiring sensitive information to be shared through "Internet-of-Things" (IoT) networks with other domestic and external devices, unnamed functionaries and various third parties. This is for data harvesting, analytics, processing, manipulation and transformation through digital re-sale to the same and other consumers in the form of unwanted, targeted advertising. The point of this identity "rendition" is to massively augment corporate profits. It is but a short step from trapping the unwitting consumer in a "smart home" to planning a similarly mediated "smart city" aimed at further massively augmenting corporate profits. This is happening, as founders of digital media from Google, Facebook, Microsoft, Amazon and Tesla either commission or become beneficiaries of "smart city" planning. However, there is evidence that such imperiousness is increasingly countered by emerging democratic critique of these new "model villages" or "company towns".
Keywords: 650; company towns; digital innovations; smart cities; surveillance capitalism